Multimodal Evoked Potentials as Potential Biomarkers of Disease Activity in Patients With Clinically Isolated Syndrome - Dziadkowiak, Edyta; Wieczorek, Małgorzata; Zagrajek, Mieszko; Chojdak-Łukasiewicz, Justyna; Gruszka, Ewa; Budrewicz, Sławomir; Pokryszko-Dragan, Anna (Frontiers in Neurology, 2022)
Objective There is an ongoing search for markers useful in monitoring and predicting disease activity at the early stage of multiple sclerosis (MS). The goals of this study were to prospectively evaluate the changes in parameters of multimodal evoked potentials (EP) and cognition within a 3-year follow-up period in patients with clinically isolated syndrome (CIS), and to assess the prognostic value of baseline findings with regard to the disease outcomes. Methods In 29 patients (20 women, nine men, mean age 31.1) multimodal (visual, brainstem auditory, somatosensory, event-related) EP and neuropsychological tests (NT) were performed at baseline (T0) and after 1 (T1) and 3 (T3) years. Their results were compared longitudinally between baseline, T1, and T3. Baseline results confirmed conversion of CIS into multiple sclerosis (MS) and disability level at T1 and T3 using multiple comparisons and a logistic regression model. Results Apart from mean N13/P16 SEP (somatosensory evoked potentials) amplitude (lower at T1 and T3 than at baseline (T0 1.02 ± 0.37 μV, T1 0.90 ± 0.26 μV, T3 0.74 ± 0.32 μV, p < 0.05 for both comparisons), no significant changes of EP or NT parameters were found in longitudinal assessment. Baseline P300 Pz latency was longer for the patients with MS than for those with CIS at T1 (352.69 vs. 325.56 ms). No predictive value was shown for any of the analyzed baseline variables with regard to conversion from CIS into MS. Significance Baseline ERP abnormalities were associated with their short-term conversion into MS. ERP are worth considering in multimodal EP evaluation at the early stage of MS.